"Let it rain" game led to 25,312 successful players and new sign up's to iShamba: Farmer information service in Kenya - CGIAR Platform for Big Data in Agriculture (2020)
The game developed in collaboration between CIAT, the Mediae development communications firm, iShamba (the digital advisory service linked to the popular "Shamba Shape Up" television program) and the game developer Usiku saw 25,312 people play the Let it rain game and subsequently sign up to the iShamba farmer mobile service to receive weekly information on selected crops and livestock, weather and market prices.